Scientific and practical research of conditions for the development of motivation and prevention of demotivators in teacher’s working activity - A. L. Kobleva (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The article studies external and internal conditions for the development of motivation for working activities. The author conducted a content analysis of scientific and practical works devoted to the study and search for the most effective ways to promote the development of teacher’s activity. In addition, the article identifies and lists the most common barriers that demotivate teachers and reduce the ability to meet the teacher’s needs of both professional and personal nature. The relevance of studying the issue of motivation in teacher’s work is considered. It is substantiated due to the fact that there is a tendency to realize the risks and threats to the future of the society as a result of devaluation of pedagogical work and prestige of teaching in various media. It should be noted that the mode of pedagogical activity is becoming increasingly multitasking and is characterized by a high degree of emotional and mental stress, which in one way or another affects the performance and psycho-emotional state of the teacher. It is no coincidence that the entire pedagogical community and modern scientists are in search of the most effective approaches to preserve the resource of teachers and maintain their motivation for professional achievements. Thus, the need and relevance of developing a system of motivation of teacher’s working activity is claimed.Goal. The study aims to determine the internal and external factors influencing the quality of teaching and to develop a matrix of the system of motivation of teacher’s working activity.Materials and methods. The study is based on content analysis and quick research method. It also employs K. Zamfir’s methodology modified by A. Rean as Motivation of professional activity, and the modeling method.Results and discussion. The psychological and pedagogical studies devoted to defining the key aspects influencing both the development of work motivation and acting as barriers to effective pedagogical activity are analyzed. In other words, demotivators are identified. A study of motivation of professional activity of teachers was conducted. As a result, groups of highly motivated teachers motivated by external positive and external negative motivation were identified. The obtained data demonstrated that most of the teaching staff are guided by internal motivation of professional activity. The practical significance of the work is confirmed by the matrix of the system of development of work motivation of a teacher, designed by the author of the article. The matrix is described in detail and presented in a figure.Conclusion. Generalization and analysis of scientific and practical aspects of labor motivation development, as well as the results of the conducted research allowed making a number of conclusions and recommendations that can be used as strategic guidelines for modeling the motivation system of the teaching staff.